Inward Eye : Transcendence in Contemporary Art. - Herbert, Lynn M.; Mayo, Marti; Ottmann, Klaus; Schjeldahl, Peter; Wordsworth, William (Houston : Contemporary Arts Museum, 2001)
Altman, Helen ; Byars, James Lee ; Celmins, Vija ; Davis, Lynn ; Fritsch, Katharina ; Gober, Robert ; Gonzalez-Torres, Felix ; Graham, Rodney ; Hamilton, Ann ; Hodgkin, Howard ; Holzer, Jenny ; Horn, Roni ; Kapoor, Anish ; Laib, Wolfgang ; de Maria, Walter ; Moffett, Donald ; Neto, Ernesto ; Pettibon, Raymond ; Ranta, Rachel ; Ray, Charles ; Richter, Gerhard ; Riley, Bridget ; Ruff, Thomas ; Shi-hua, Qiu ; Steir, Pat ; Topchy, Nestor ; Turrell, James ; Viola, Bill ; Wilson, Robert
biog., bibliog. p. 100-107
Engels
The Inward Eye : Transcendence in Contemporary Art, Contemporary Arts Museum, Houston, December 8, 2001 - February 17, 2002
boek